2023
DOI: 10.1155/2023/7123826
|View full text |Cite
|
Sign up to set email alerts
|

Vermicompost and NPSZnB Fertilizer Levels on Maize (Zea mays L.) Growth, Yield Component, and Yield at Guto Gida, Western Ethiopia

Abstract: The application of organic and inorganic fertilizers together increases crop productivity and soil fertility. However, it is crucial to identify the combined application level. A field experiment was carried out in the Guto Gida district in 2021 to determine the effect of vermicompost levels and chemically mixed NPSZnB fertilizer rates on the growth and yield of maize. Four vermicompost levels (0, 2.5, 5, and 7.5 t·ha−1) combined with four artificial NPSZnB fertilizer rates (0, 50, 100, and 150 kg·ha−1) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The results concluded that the integrated application of FYM with 75 per cent RDN could be used to sustain wheat productivity and maintain soil fertility which otherwise deteriorates due to the sole application of inorganic fertilizers". Tufa [40] conducted an experiment to study the vermicompost N, P, S, Zn, B fertilizer levels on maize (Zea mays L.) growth, yield component and yield at Guto Gida, Western Ethiopia. From this experiment, it is concluded that the integrated applications of vermicompost at 5 t/ha and NPSZnB fertilizer at 100 kg/ha increased maize yield by about 10.36 per cent, with a net benefit of 140486.00 ETB/ha and a marginal rate of return of 797.98 per cent.…”
Section: Effect Of Integrated Nutrient Management On Plant Growth Yie...mentioning
confidence: 99%
“…The results concluded that the integrated application of FYM with 75 per cent RDN could be used to sustain wheat productivity and maintain soil fertility which otherwise deteriorates due to the sole application of inorganic fertilizers". Tufa [40] conducted an experiment to study the vermicompost N, P, S, Zn, B fertilizer levels on maize (Zea mays L.) growth, yield component and yield at Guto Gida, Western Ethiopia. From this experiment, it is concluded that the integrated applications of vermicompost at 5 t/ha and NPSZnB fertilizer at 100 kg/ha increased maize yield by about 10.36 per cent, with a net benefit of 140486.00 ETB/ha and a marginal rate of return of 797.98 per cent.…”
Section: Effect Of Integrated Nutrient Management On Plant Growth Yie...mentioning
confidence: 99%
“…In order to investigate the effects of vermicompost N, P, S, Zn, and B fertiliser levels on the growth, yield component, and yield of maize (Zea mays L.), Tufa [33] carried out an experiment in Guto Gida, Western Ethiopia. With a net benefit of 140486.00 ETB/ha and a marginal rate of return of 797.98 percent, the integrated applications of vermi-compost at 5 t/ha and NPSZnB fertiliser at 100 kg/ha boosted maize production by approximately 10.36%, according to the results of this experiment.…”
Section: Effect Of Integrated Nutrient Management On Plant Growth Yie...mentioning
confidence: 99%